Education on the Use of Biopore Infiltration Holes for Flood Prevention at SDN 100 Kendari, Kambu Village, Kambu District, Southeast Sulawesi - La Ode Siwi; Ridwan Adi Surya; Wa Ode Hastiani Fahidu; Ema Hermawati Garusu; Abdul Manan; La Ode Muhammad Erif; Lies Indriyani; Sahindomi Bana; La Gandri; Muhammad Saleh Qadri (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This program aimed to enhance elementary students’ understanding of biopore infiltration holes as a low-cost solution for mitigating waterlogging and addressing inadequate drainage at SDN 100 Kendari. Method: The intervention combined interactive lectures, live demonstrations, hands-on construction, and guided discussions. Learning outcomes were evaluated using standardized pre-test and post-test instruments. Practical Applications: The activity enabled students to construct functional biopores that improve groundwater absorption, reduce surface runoff, and facilitate organic waste management, providing a replicable framework for school-based environmental management. Conclusion: Student comprehension significantly increased from 10–20% to 80–90%. These results demonstrate that participatory environmental education effectively fosters ecological literacy and supports localized flood mitigation in urban school settings.